Gereja Katolik Santa Perawan Maria Yang Terkandung Tanpa Noda Banjarmasin: Sejarah dan Perkembangannya - L, Maria Dwi Oktavira; Subroto, Wisnu; Mardiani, Fitri (Lambung Mangkurat University, 2021)
South Kalimantan is an area with a majority Islamic population, but in the majority religious tolerance has proven strong, the evidence is in the form of places of worship for non-Muslim residents. One proof is the Catholic Church in Kelayan which has been established since 1939, so the development of this church is interesting to study more deeply and more broadly. This study aims to describe the history of the establishment, development of activities, and services of the Catholic Church of the Immaculate Conception of the Blessed Virgin Mary from 1939-2020. The method used in this study uses historical methods consisting of Heuristics, Criticism, Interpretation, and Historiography. Heuristics, the data collection stage, both primary and secondary data, data sources are obtained through 3 things, namely oral sources obtained from interviews, written sources obtained from books, journals, articles, and object sources obtained by researchers when viewing the building or the state of the church. After the data is collected, the next stage is source criticism, the next is interpretation and the last is the historiography or writing stage. The results of this research that the Catholic Church has been established for 81 years, so it has a lot of history that is engraved, starting from a priest named Mgr, Kusters MSF who wants to expand the teachings of Catholicism in South Kalimantan and has a mission to establish a Catholic Church in Kelayan which is still still stands firmly in the West Kelayan Village